Os parques lineares como catalisadores de processos de gentrificação verde: uma análise do programa João Pessoa Sustentável e a implementação do Parque Linear Jaguaribe - Silva, Maria Júlia Laurentino (2022)
The present work seeks to understand the implementation of the Parque Linear Jaguaribe in the city of João Pessoa, with the purpose of analyzing the development of the green gentrification process in its receiving territory. For that, a bibliographical and documental research on the subject was carried out, using the comparative methodology of the social sciences. Added to this, the use of concepts of psychosphere and technosphere, by Milton Santos, used in his analysis of geographic space, which are used here to identify the global agenda of urban sustainability and its spatial manifestations. Where there is the agenda as an example of the first conception and the green infrastructures and linear parks, as an example of the second. It appears that the city of João Pessoa is inserted in a process of marketing production of its space, provided by the financing of the Inter-American Development Bank-IDB, through the Sustainable and Emerging Cities Initiative, which in 2013 included the city of João Pessoa, resulting in the creation of the “Sustainable João Pessoa Program”. It is pointed out that once the partnership between the IDB and the PMJP was closed, several signs of a green gentrification process were found, linked to the implementation of the Jaguaribe Linear Park and the removal of the communities settled along the middle course of the Jaguaribe River . This conclusion was possible through case studies, as well as the analysis of documents from the Program itself, on the intentions of valuing the area, removing more than 800 families.